Association of CD1a‐positive dendritic cells with papillary thyroid carcinoma in thyroid fine‐needle aspirations1. Issue 4 (5th October 2012) - Pusztaszeri, Marc P.; Sadow, Peter M.; Faquin, William C.
Abstract BACKGROUND: In contrast to other primary thyroid neoplasms and benign thyroid tissue, it has been demonstrated histologically that dendritic cells (DCs) are associated with papillary thyroid carcinoma (PTC). However, the presence and potential diagnostic value of DCs in thyroid fine‐needle aspirations (FNAs) have not been previously described. METHODS: The authors quantitatively assessed for the presence of DCs that were positive for cluster of differentiation 1a (CD1a) (a 43‐49 kD protein expressed on DCs and cortical thymocytes) in cytologic samples of histologically confirmed PTC (n = 31) and in a control group of benign thyroid nodules (BTNs) (n = 29) using immunocytochemical staining with antibodies against CD1a. A subset of the corresponding PTCs (n = 11) and BTNs (n = 10) from surgical resection specimens also were assessed immunohistochemically for both CD1a and Langerin (a type II transmembrane cell surface receptor produced by Langerhans cells). RESULTS: CD1a‐positive DCs were identified in 97% PTCs (n = 30 of 31 PTCs) in thyroid FNA specimens. DCs were largely present in 2 distinct patterns: either as isolated DCs in the background (n = 29 of 31) and/or associated with tumor cells (n = 30 of 31). Tumor‐associated DCs (mean ± standard deviation: 6.44 ± 6.13 DCs per tumor cluster) exhibited multiple dendritic cytoplasmic processes extending over and between malignant cells within groups. The 3 PTC cases with the least DCs corresponded to the follicular variant at excision. In contrast, only 31% of BTNs (n = 9 of 29 BTNs; P = .0048) contained CD1a‐positive DCs. When DCs were present in BTN, they were isolated primarily in the background (27%; n = 8 of 29), although 17% of BTNs (n = 5 of 29) contained rare DCs among thyrocytes, revealing both patterns in 4 cases. Both thyrocyte‐associated DCs and background DCs were more numerous in PTC FNAs than in BTN FNAs, but only the thyrocyte‐associated group of DCs was statistically significant (P < .0001 and P = .1173, respectively). Similar findings were reported in histologic samples in which all PTCs examined (n = 11 of 11) contained both CD1a‐positive and Langerin‐positive DCs; only 20% of BTNs (n = 2 of 10) contained rare DCs. CONCLUSIONS: CD1a‐positive DCs were present in FNA specimens of PTC, typically in close association with tumor cells, whereas they were rare in BTNs. The increased presence of CD1a‐positive DCs in PTC may be a useful diagnostic adjuvant. Cancer (Cancer Cytopathol) 2013;121:206–213. © 2012 American Cancer Society.